Movement on the Silk Road: China's "Belt and Road" initiative as an incentive for intergovernmental cooperation and reforms at Central Asia's borders - Sebastian Schiek (Stiftung Wissenschaft und Politik (SWP), 2017)
The aim of China's Silk Road Initiative is to bolster both its international legitimacy and its geopolitical power. One important element of the initiative is the plan to transport export goods by high-speed train to Western Europe. In order to ensure that rapid freight transit is profitable in the long term, Beijing believes that major changes are needed along the borders of Central Asia. The Chinese government has explicitly called for reforms from its partner countries, including Kazakhstan and Uzbekistan, meaning greater economic openness, regional cooperation and modern border crossings. The opportunities for change in Central Asia are now much better than in the past. Kazakhstan and Uzbekistan's growth models have reached their limits and both countries are now under considerable pressure to reform. Uzbekistan's new president has also announced promising new reform policies. In addition, political rule in Central Asia is now more institutionalized and, therefore, increasing scope for partial reforms. Furthermore, since the beginning of the century, China has become a powerful actor in the region. Unlike Russia, it is interested in better intra-regional cooperation in Central Asia and, ultimately, the Silk Road Initiative provides incentives for reform and greater cooperation at the borders. For Germany and the EU, it might be worth discussing common interests with China and how synergies could be used to positively influence the reforms. The EU can draw on the knowledge and experience gained from its long-term project on border reforms in Central Asia.
Keywords: 320